Innovative Tools for Mechanobiology: Unraveling Outside-In and Inside-Out Mechanotransduction - Mohammed, Danahe; Versaevel, Marie; Bruyère, Céline; Alaimo, Laura; Luciano, Marine; Vercruysse, Eléonore; Procès, Anthony; Gabriele, Sylvain (Frontiers in Bioengineering and Biotechnology, 2019)
Cells and tissues can sense and react to the modifications of the physico-chemical properties of the extracellular environment (ECM) through integrin-based adhesion sites and adapt their physiological response in a process called mechanotransduction. Due to their critical localization at the cell-ECM interface, transmembrane integrins are mediators of bidirectional signaling, playing a key role in « outside-in » and « inside-out » signal transduction. After presenting the basic conceptual fundamentals related to the field of mechanobiology, we review the current state-of-the-art technologies that facilitate the understanding of mechanotransduction signaling pathways. Finally, we highlight innovative technological developments that can help to advance our understanding of the molecular mechanisms involved in nuclear mechanotransduction.